0329 Recording of Respiration by Analysis of High Resolution Actigraphy for Sleep Apnea Diagnosis In Field Studies. (27th April 2018) - Penzel, T; Kluge, M; Glos, M; Kantelhardt, J W; Bartsch, R; Zinkhan, M; Fietze, I
Abstract: Introduction: Large field studies now check for the prevalence of sleep apnea using simplified low cost recording technologies. A national field study on 200.000 persons investigates a subset of 40.000 persons with actigraphy and single-lead 24-hour ECG to check for arrhythmias and sleep apnea. Methods: In order to validate the actigraphy and 24-hour ECG recording 500 patients referred to polysomnography in a sleep center are equipped in parallel with actigraphy (one on the wrist and one on the hip) and a single-lead 24-hour ECG. For actigraphy on the wrist a Somnowatch plus (128 Hz sampling) with 3D acceleration was used. For actigraphy on the hip a GT3X+, primarily applied for estimating energy consumption, was used. ECG was analyzed for heart rate variability and electrocardiographic derived respiration (EDR) for all slep stages. Actigraphy was analyzed for threshold passing and in addition with spectral analysis in 30-second epochs in parallel with PSG sleep scorings. Results: The validation study has now completed 155 patients. Mean age of subjects is 45.7 years. Mean AHI in this sleep center population was 12 /hour. Analysis of cyclical variation of heart rate and EDR allows to detect sleep apnea events from single-lead ECG recordings. In addition, it was possible to detect respiration from high resolution actigraphy both from wrist and hip placed devices by applying a frequency analysis on 30-second epochs. Dection of respration is best for stage N3. Conclusion: The surprising result showed that actigraphy allowed to detect respiration with high accuracy during sleep and during periods with low activity. With this it appears possible to detect apnea events as well. To validate apnea recognition more subjects with apnea are needed. If successful this will allow to improve ECG based apnea detection and will allow to apply simple recording technology on really large epidemiological cohort studies to check prevalence in unselected groups of subjects. Support (If Any): Supported by German Israel Foundation (GIF) grant no I-1372-303.7/2016.